Ten Dimensions of Inclusion: Non-Catholic Students in Catholic Schools - Donlevy, J. Kent (Catholic Education: A Journal of Inquiry and Practice, 2007)
This article addresses the inclusion of non-Catholic students in Catholic schools. It provides a brief review of the literature on inclusion and the results of a study of inclusion from the perspectives of Catholic students and Catholic teachers in four Western Canadian urban Catholic high schools. The study employed grounded theory as its methodology and focus groups as well as documentary analysis as its methods. The results of the qualitative study indicate, among other things, that there are at least 10 dimensions to inclusion: pedagogical, social, psychological, racial, cultural, spiritual, political, financial, legal, and philosophical. Moreover, the dimensions form an interactive matrix which is of great importance to Catholic schools.